Evaluation of AVHRR cloud detection at Dome Fuji Station, Antarctica - ヤマノウチ, タカシ; ヒラサワ, ナオヒコ; カドサキ, ガク; ハヤシ, マサヒコ; Yamanouchi, Takashi; Hirasawa, Naohiko; Kadosaki, Gaku; Hayashi, Masahiko (National Institute of Polar Research, 2000)
P(論文) A polar cloud detection algorithm, which uses the scatter diagram of brightness temperature and brightness temperature difference of 10μm split window channels of AVHRR, was evaluated at Dome Fuji Station, Antarctica. Among the data of June 1997,most of the cloudy scenes were effectively detectable. However, some of the cloudy scenes were not detectable with only the scatter diagram. It was found that additional information on the temporal variation of brightness temperature permitted effective detection. departmental bulletin paper